Synthesis, characterization and electrical properties of hybrid Zn2GeO4–ZnO beaded nanowire arrays - Mukherjee, Bablu (2013)
We report the syntheses of vertically aligned, beaded zinc germinate (Zn2GeO4)/zinc oxide (ZnO) hybrid nanowire arrays via a catalyst-free approach. Vertically aligned ZnO nanowire is used as a lattice matching reactive template for the growth of Zn2GeO4/ZnO nanowire. The morphology and structure of the as-prepared samples were characterized using X-ray diffractometry (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDS). TEM studies revealed the beaded microstructures of the Zn2GeO4/ZnO nanowire. The thickness and microstructures of crystalline beads could be easily controlled by tuning the growth duration and temperature. The photoluminescence spectrum of the Zn2GeO4/ZnO nanowires is composed of two peaks, i.e., the ultraviolet (UV) peak and the defect peak. For longer treatment duration of the samples, both the UV and defect peak intensities decrease dramatically. One application of the as-prepared Zn2GeO4/ZnO nanowire is to use the nanowire as template for the growth of three-dimensionally (3D) aligned, high-density ZnO nanobranches en route to hierarchical structure. The study of field emission properties of the as-prepared samples revealed the low turn-on voltage and high current density electron emission from the 3D ZnO nanobranches as compared to the ZnO nanowires and Zn2GeO4/ZnO nanowires. Furthermore, the electrical transport behavior of single hybrid nanowire device indicates the formation of back-to-back Schottky barriers (SBs) formation at the contacts and its application in white-light response has been demonstrated.